Aplikasi Sistem informasi Pengenalan Tanaman Obat Keluarga Berbasis Android - Machudor Yusman (Universitas Mitra Indonesia, 2021)
AbstractThe development of technology in information and communication has increased developments in the world, including in the health sector. One that is developing and commonly implemented in the world of health, one of which is pharmaceutical health, especially digital-based medicine information technology. Regarding the types of medicinal plants recorded in a manual book, so that in their daily use, people tend not to have time to look in books about the benefits of the Application for Introduction to Family Medicinal Plants, besides that the user interface is still very simple so that it does not attract the public's interest to read. Another problem that occurs is the difficulty of finding information about plants and what benefits are needed and the lack of means of promotion or introduction of Family Medicinal Plants to the community. From the description above, the authors propose to design an android-based application including the introduction of various medicinal plants as well as a means of promotion so that every family has a living pharmacy and public health is increasing. Based on the results of the research, the application of family medicinal plant recognition can help users in recognizing the types of medicinal plants and as a means of promotion so that each family has a live pharmacy and based on the results of tests carried out on the system shows that the application has been running well and in accordance with what is expected